Les hauts de hurlevent : Abismos de pasion - Buñuel, Luis, 1900-1983; Alejandro, Julio, 1906-1995; Maiuri, Arduino, 1916-1984; Dancigers, Oscar, -1976; Dilian, Irasema, 1924-1996; Mistral, Jorge, 1920-1972; Prado, Lilia; Alonzo, Ernesto; Brontë, Emily, 1818-1848 (Collection Films du siècle., 2006)
Buñuel transforms Bronte's Yorkshire moors into a Mexican hacienda, and Heathcliff and Cathy become Alejandro and Catarina (Katy), who engage in a passionate, doomed love affair with a power that obliterates all convention and transcends even death.